Pretty Dyana - Mitić, Boris (Dribbling Pictures, 2003)
Duration: 00:44:00 An intimate look at Roma refugees in a Belgrade suburb who make a living by transforming Citroën's classic 2cv and Dyane cars into Mad Max-like recycling vehicles, which they use to collect cardboard, bottles and scrap metal These modern horses are much more efficient than the cart-pushing competition, but even more important -- they also mean freedom, hope and style for their crafty owners. Even the car batteries are used as power generators in order to get some light, watch TV and recharge cell-phones! Almost an alchemist's dream come true! But the police don't always find these strange vehicles funny…